2021
DOI: 10.1038/s41598-021-85455-4
|View full text |Cite
|
Sign up to set email alerts
|

Aging selectively dampens oscillation of lipid abundance in white and brown adipose tissue

Abstract: Lipid metabolism is under the control of the circadian system and circadian dysregulation has been linked to obesity and dyslipidemia. These factors and outcomes have also been associated to, or affected by, the process of aging. Here, we investigated whether murine white (WAT) and brown (BAT) adipose tissue lipids exhibit rhythmicity and if this is affected by aging. To this end, we have measured the 24 h lipid profiles of WAT and BAT using a global lipidomics analysis of > 1100 lipids. We observed rhythmi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…Cluster 3 (peak ZT16) contained 11 of the 13 oscillating FAs and eight of the nine oscillating monoacylglycerols (MGs; Figure 3 B). These data are in concordance with our previous observations in young mice [ 34 ], and consistent with a peak in lipolytic activity at the onset of the dark (active) phase as indicated by the RNA-sequencing data and previous functional data on TG-derived FA-uptake by BAT [ 13 ], as both intracellular and extracellular lipolysis yield MGs and FAs. Of note, five of the identified FAs within cluster 3 are poly-unsaturated FAs (PUFAs), which are known ligands for PPARγ [ 35 ] and UCP1 [ 36 ] and therefore likely contribute to thermogenic activation of the tissue followed by the uptake and storage of TG-derived FA from the circulation.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Cluster 3 (peak ZT16) contained 11 of the 13 oscillating FAs and eight of the nine oscillating monoacylglycerols (MGs; Figure 3 B). These data are in concordance with our previous observations in young mice [ 34 ], and consistent with a peak in lipolytic activity at the onset of the dark (active) phase as indicated by the RNA-sequencing data and previous functional data on TG-derived FA-uptake by BAT [ 13 ], as both intracellular and extracellular lipolysis yield MGs and FAs. Of note, five of the identified FAs within cluster 3 are poly-unsaturated FAs (PUFAs), which are known ligands for PPARγ [ 35 ] and UCP1 [ 36 ] and therefore likely contribute to thermogenic activation of the tissue followed by the uptake and storage of TG-derived FA from the circulation.…”
Section: Resultssupporting
confidence: 93%
“…Lipidomics was performed as previously described [ 34 , 68 ], with minor adjustments. Briefly, the following amounts of internal standards dissolved in 1:1 (v/v) methanol:chloroform were added to each sample: bis(monoacylglycero)phosphate BMP(14:0)2 (0.2 nmol), ceramide-1-phosphate C1P (d18:1/12:0) (0.127 nmol), D 7 -cholesteryl ester CE(16:0) (2 nmol), ceramide Cer(d18:1/12:0) (0.118 nmol), ceramide Cer(d18:1/25:0) (0.130 nmol), cardiolipin CL(14:0)4 (0.1 nmol), diacylglycerol DAG(14:0)2 (0.5 nmol), glucose ceramide GlcCer(d18:1/12:0) (0.126 nmol), lactose ceramide LacCer(d18:1/12:0) (0.129 nmol), lysophosphatidicacid LPA(14:0) (0.1 nmol), lysophosphatidylcholine LPC(14:0) (0.5 nmol), lysophosphatidylethanolamine LPE(14:0) (0.1 nmol), lysophosphatidylglycerol LPG(14:0) (0.02 nmol), phosphatidic acid PA(14:0)2 (0.5 nmol), phosphatidylcholine PC(14:0)2 (2 nmol), phosphatidylethanolamine PE(14:0)2 (0.5 nmol), phosphatidylglycerol PG(14:0)2 (0.1 nmol), phosphatidylinositol PI(8:0)2 (0.5 nmol), phosphatidylserine PS(14:0)2 (5 nmol), sphinganine 1-phosphate S1P(d17:0) (0.124 nmol), sphinganine-1-phosphate S1P(d17:1) (0.125 nmol), ceramide phosphocholines SM(d18:1/12:0) (2.129 nmol), sphingosine SPH(d17:0) (0.125 nmol), sphingosine SPH(d17:1) (0.125 nmol), triacylglycerol TAG(14:0)2 (0.5 nmol).…”
Section: Methodsmentioning
confidence: 99%
“…There are now multiple studies across several organ systems demonstrating diurnal variations of lipids in response to different conditions. 12,13,[31][32][33] In our study, which was the first to examine the effects of a CJ protocol on mouse pancreatic transcriptome, we found that several lipid metabolism pathways were altered and genes in these pathways exhibited a shift in the phase (peak 24-hour expression) of their expression. 14 Therefore, we sought to first understand whether there are diurnal variations in the pancreatic lipidome and subsequently whether there are changes in the pancreatic lipidome in response to CJ conditions.…”
Section: Discussionmentioning
confidence: 71%
“…BAT displays pronounced diurnal variation in transcriptional activity, lipid content, and nutrient uptake [ 17 , 18 , 24 , 25 ], of which the latter highly contributes to the beneficial effects of BAT on cardiometabolic health [ 10 , 11 ]. While previous studies show an age-related dampening in oscillations of mRNA levels and lipid abundance in BAT [ 25 , 26 ], it is unknown how aging affects diurnal nutrient uptake by BAT.…”
Section: Discussionmentioning
confidence: 99%
“…BAT displays pronounced diurnal variation in transcriptional activity, lipid content, and nutrient uptake [ 17 , 18 , 24 , 25 ], of which the latter highly contributes to the beneficial effects of BAT on cardiometabolic health [ 10 , 11 ]. While previous studies show an age-related dampening in oscillations of mRNA levels and lipid abundance in BAT [ 25 , 26 ], it is unknown how aging affects diurnal nutrient uptake by BAT. Here we demonstrated that with age this rhythm of nutrient uptake is attenuated characterized by a selective reduction in TG-derived FA uptake at the onset of the dark phase in specifically female mice, an effect that was accompanied by elevated plasma lipid levels and by adipose tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%